Synthesis and characterization of multi-walled carbon nanotubes decorated with hydroxyapatite. Issue 6 (3rd June 2021) - David, Madalina Elena; Grigorescu, Ramona Marina; Iancu, Lorena; Andrei, Elena Ramona; Somoghi, Raluca; Frone, Adriana Nicoleta; Atkinson, Irina; Predoana, Luminita; Nicoara, Adrian-Ionut; Ion, Rodica-Mariana
Abstract: In this paper, multi-walled carbon nanotubes have been prepared at low synthesis temperatures and without high pressure by a simple chemical route. Fourier transformed infrared spectroscopy, Raman spectroscopy and X-ray diffraction analysis was used to determine the purity of the synthetized compound. Also, by transmission electron microscopy and atomic force microscopy, a diameter between 9 nm and 43 nm and approximately 500–600 nm in length of multi-walled carbon nanotubes, was confirmed. Further, the multi-walled carbon nanotubes functionalized with negative charged functional groups (anionic groups) were decorated with hydroxyapatite by co-precipitation method. The decoration of multi-walled carbon nanotubes with hydroxyapatite was confirmed by transmission electron microscopy, Fourier transformed infrared spectroscopy and X-ray diffraction analysis. Also, energy-dispersive X-ray analysis proved the successfully obtaining of the nanocomposites. The simple method presented here may be extended to synthesize other composites based on coated multi-walled carbon nanotubes.